2019
DOI: 10.2147/cmar.s224097
|View full text |Cite
|
Sign up to set email alerts
|

<p>Proton Pump Inhibitors Modulate Transport Of Doxorubicin And Its Liposomal Form Into 2D And 3D Breast Cancer Cell Cultures</p>

Abstract: PurposeThe purpose of our study was to evaluate the influence of two PPIs (omeprazole (OME) and lansoprazole (LANSO)) on weakly basic anticancer drug doxorubicin (DOX) and pegylated liposomal doxorubicin (PLD) delivery to monolayer-cultured 4T1 murine breast cancer cells and tumor spheroids.MethodsThe effect of PPIs on cell viability was evaluated by MTT assay. 3D cell cultures (spheroids) were formed using 3D bioprinting method. DOX and PLD penetration into cancer cells and spheroids at pH 6.0 and 7.4 was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
(38 reference statements)
1
7
0
Order By: Relevance
“…In our in vitro study, the 2-h pretreatment of lansoprazole had no consistent effect on the observed IC 50 values for DOXs or DOX PL in the examined cell lines. One plausible explanation is that slightly acidic conditions (pH 6) are required in order to have a PPI-effect on DOX potency [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our in vitro study, the 2-h pretreatment of lansoprazole had no consistent effect on the observed IC 50 values for DOXs or DOX PL in the examined cell lines. One plausible explanation is that slightly acidic conditions (pH 6) are required in order to have a PPI-effect on DOX potency [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…As pH levels decrease, metalloproteinases become activated, destroying cell interactions which facilitates tumor migration and invasion [46]. Acidic microenvironment causes the "ion trapping" phenomenon, process in which basic anticancer drugs are transformed into a cation substance, reducing their transmembrane permeability and, consequently, their effectiveness [47]. Immune cells such as macrophages, neutrophils, mast cells, myeloid-derived suppressor cells, and natural killer cells, secret many soluble factors that promote immunosuppression, angiogenesis, chronic inflammation, and drug resistance [43,[48][49][50].…”
Section: Tumor Microenvironment As Pathophysiologic Barrier To Anticancer Therapymentioning
confidence: 99%
“…In fact, numerous preclinical studies and some ongoing clinical trials can be found in the literature about the usefulness of these PPIs to increase the pH e and avoid MDR in cancer 17 , 23 , 32 . Paškevičiūtė and Petrikaitė 33 reported the use of two PPIs, omeprazole (OPZ) and lansoprazole (LPZ), to enhance delivery of doxorubicin in its free form or inside PEGylated liposomes to 4T1 breast cancer cells and 3D cell cultures (4T1) at simulated pH e of 6.0, not observing this effect at physiological pH and being LPZ more effective than OPZ.…”
Section: Proton Transport Inhibitors and Nanocarriersmentioning
confidence: 99%
“…Despite the advantages of using targeted nanocarriers in combination with V-ATPase inhibitors to enhance the delivery of weakly basic chemotherapeutic agents, to the best of our knowledge, apart from the reports by Paškevičiūtė 33 and Bhattacharya 37 ( Table S1 ), no other papers have been published in this regard.…”
Section: Proton Transport Inhibitors and Nanocarriersmentioning
confidence: 99%